Effect of BAU-Biofungicide and Plant Extracts on Seedling Vigour of Maize (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted in Seed Pathology Center, Bangladesh Agricultural University, Mymensingh to determine the efficacy of biocontrol means (BAU-Biofungicide, Garlic extract and Neem extract) and vigour index of seedling for controlling the seedborne fungal diseases of maize. In laboratory experiment, the prevalence of seed-borne fungi associated with maize cultivar cv. BARI Bhutta - 6 were investigated by blotter method. The identified fungi species were A. niger, A. flavus, Fusarium sp., P. oxalicum, C. lunata and R. stolonifer. The test materials were treated with BAU-Biofungicide @ 2.5% of seed weight, neem extract @ 1:2 w/v and 1:3 w/v and garlic extract @ 1:2 w/v and 1:3 w/v to control the pathogens. Significantly, the highest germination (87.%) and the lowest incidence of pathogen (4%) was recorded in BAU-Biofungicide treated seed The maize seeds treated by BAU- Biofungicide also show the higher vigour index (2856) followed by neem extract (1:2) treated seed (2621) after germination.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14602 J. Environ. Sci. & Natural Resources, 5(2): 59-61 2012